2017
DOI: 10.1016/j.anpedi.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Infecciones virales respiratorias en una cohorte de niños durante el primer año de vida y su papel en el desarrollo de sibilancias

Abstract: In our series, severe respiratory infections leading to hospitalisation in the first months of life are risk factors for developing wheezing, but not in the case of mild RV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The authors showed that infants who required hospitalization for their first viral infection had an increased risk of developing recurrent wheezing, compared to infants whose first viral infection was mild or asymptomatic. 26 Furthermore, Bønnelykke et al 16 evaluated the association between viral respiratory infections (HRSV, rhinovirus, among others) and bacterial infections in infants, and the development of asthma in childhood. They concluded that the total number of respiratory infections suffered at an early age was a risk factor for developing asthma, regardless of the specific causal agent.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that infants who required hospitalization for their first viral infection had an increased risk of developing recurrent wheezing, compared to infants whose first viral infection was mild or asymptomatic. 26 Furthermore, Bønnelykke et al 16 evaluated the association between viral respiratory infections (HRSV, rhinovirus, among others) and bacterial infections in infants, and the development of asthma in childhood. They concluded that the total number of respiratory infections suffered at an early age was a risk factor for developing asthma, regardless of the specific causal agent.…”
Section: Discussionmentioning
confidence: 99%
“…Several severe AB phenotypes have already been identified, and research in this field continues to grow. 36 Thus, some of the current evidence suggests that AB due to rhinovirus has specific clinical and epidemiological characteristics 37 as well as a different long-term prognosis in relation to atopic asthma. 38,39 A viral aetiology is emphasised in descriptions of AB or specifically included in the definitions of disease proposed by some guidelines, 6,9,25---27,34 and many clinical trials only enrol children with infection by RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Varios fenotipos de BA grave han sido ya identificados y continúa la investigación en este campo 36 . En este sentido, algunos datos hacen pensar que la BA debida a infección por rinovirus tiene características clínicas y epidemiológicas particulares 37 , y un diferente pronóstico a largo plazo en cuanto a su relación con el asma atópico 38,39 . La etiología vírica se destaca en las descripciones de la enfermedad o se incorpora específicamente en la definición en algunas guías 6,9,25---27,34 , y muchos ensayos clínicos incluyen solo niños con infección por VRS 7 .…”
Section: Discussionunclassified